«FEAST OF TRUMPETS» BY YEVHEN STANKOVYCH: MONOTIMBRICAL ENSEMBLE AS A SPACE FOR CREATIVE EXPERIMENTATION - Fyk, Yurii; Sapozhnik, Olga (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of studying «Feast of Trumpets» for 16 unaccompanied trumpets by Ye. Stankovych lies in its representation of a hypothetical space for the author’s daring creative experiment with a monotimbral ensemble. This aspect organically correlates with the composer’s profile, distinguished by an integrative approach to genre and style, where timbral solutions emerge as one of the key expressive means. Within the broader context of Ye. Stankovych’s oeuvre, his chamber music often serves as a unique «laboratory» for testing innovative compositional solutions. The main objective of the study is to investigate the monotimbral ensemble as a space for creative experiment in «Feast of Trumpets» by Ye. Stankovych. The methodology includes the following methods: a systemic approach (for analyzing the work as a holistic artistic system); music-theoretical (for studying the harmonic, melodic, rhythmic, and textural organization of the piece); instrument-specific (focused on researching the specifics of trumpet usage within a monotimbral ensemble, identifying extended performance techniques and their impact on the sonic palette); and a hermeneutical approach (used for a deeper understanding and interpretation of the compositional intent). Despite its classification as a chamber work, confirmed by its placement in the composer’s catalog and the absence of a mandatory conductor (though existing recordings often feature one, highlighting its orchestral and monumental qualities), «Feast of trumpets» represents a unique example of an experiment with a monotimbral ensemble. The composition for sixteen trumpets is an unusual phenomenon, as such a concentration of instruments from a single timbral group is rarely encountered even in large brass orchestras. The score of «Feast of trumpets» utilizes eight staves, with each pair of trumpets primarily playing in unison, creating a powerful and rich sound. Some episodes are marked by the composer’s «divisi» remark, introducing timbral and textural variety into the ensemble’s monolithic sound. The work’s duration, under five minutes, formally categorizes it as a small musical form. However, the profoundness of its concept, the monumentality of its sound fabric, and its strong emotional impact on the listener unequivocally allow it to be characterized as a micro-symphonic sketch. It is quite plausible that this work could organically integrate into the architectonics of an expanded symphony, serving as an interlude or even a culminating episode. The form of «Feast of trumpets» clearly delineates a three-part structure. The first section presents an impressive complex of cluster formations that span a wide sonic range, creating a maximally volumetric sound space. A characteristic feature of this section is the frequent meter changes (3/4, 4/4, 5/4), contributing to a sense of boundlessness and allencompassing nature. The sound palette evokes certain allusions and parallels with the introduction to symphonic poem «Also sprach Zarathustra» by Richard Strauss underscoring the global scale of the compositional design. The middle section of the composition consists of two contrasting thematic blocks. The first is an energetic, rapid, synchronous movement, distinguished by a triplet rhythm and an ascending melodic direction. The massive rhythmic unisons of the trumpets in this episode recall the historical nature of the trumpet as a signaling instrument, imbued with heroism and dynamism. The second thematic block of the middle section is a distinct quasi-folk chant characterized by the use of sustained tones. The layering of trumpet parts in this episode leads to the formation of a unique polyphonic texture, enriching the monotimbral sound with new expressive nuances. The recapitulation returns the listener to the initial emotional state of the work. The musical material of the first section is presented in a condensed form but with significantly amplified dynamics, reaching a climactic tension and concluding the composition on a high emotional note. Results and conclusions. «Feast of trumpets» by Ye. Stankovych vividly exemplifies how a deliberate limitation of the timbral palette can become not an obstacle, but a powerful stimulus for creative experiment. The composer masterfully utilizes the unique acoustic properties of brass instruments, their ability to create both dense cluster sounds and expressive melodic lines, as well as rich rhythmic figurations and polyphonic elements. Through this, the composer achieves a monumental and deeply emotional impact, despite the work’s formal brevity and monotimbrality. The piece rightfully holds a special place in the composer’s chamber heritage, demonstrating his courage in seeking new expressive means and an original approach to instrumental possibilities.